2020
DOI: 10.1002/jor.24841
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a self‐assembling peptide hydrogel scaffold for meniscal defect: An in vivo study in a rabbit model

Abstract: The inner avascular zone of the meniscus has limited healing capacity as the area is poorly vascularized. Although peptide hydrogels have been reported to regenerate bone and cartilage, their effect on meniscus regeneration remains unknown. We tested whether the self-assembling peptide hydrogel scaffold KI24RGDS stays in the meniscal lesion and facilitates meniscal repair and regeneration in an induced rabbit meniscal defect model. Full-thickness (2.0 mm diameter) cylindrical defects were introduced into the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…They can also be obtained via the self-assembly of small molecules. Peptide molecules with the ability to self-assemble into physically cross-linked fibre-like structures are ideal alternatives [60] , [61] . Peptide self-assembled hydrogels have outstanding advantages, such that they are biocompatible, biodegradable, and nontoxic [62] .…”
Section: Driving Forces and Morphology Of Self-assembled Peptide Nano...mentioning
confidence: 99%
“…They can also be obtained via the self-assembly of small molecules. Peptide molecules with the ability to self-assemble into physically cross-linked fibre-like structures are ideal alternatives [60] , [61] . Peptide self-assembled hydrogels have outstanding advantages, such that they are biocompatible, biodegradable, and nontoxic [62] .…”
Section: Driving Forces and Morphology Of Self-assembled Peptide Nano...mentioning
confidence: 99%
“…RGD peptides improved growth of cells, while the anti-VEGF-R2 DNA aptamer seemed to promote cell viability, and also angiogenesis by tube formation by endothelial cells, useful for advanced wound healing applications. Okuno et al tested the potential applications of a hydrogel scaffold KI24RGDS to facilitate meniscal regeneration in an induced rabbit meniscal defect model [ 154 ]. They reported a high biocompatibility of the KI24RGDS hydrogel with strong stiffness, possessing a similar native extracellular matrix useful for cell adhesion and proliferation.…”
Section: Biomedical Applications Of Peptide-based Hydrogelsmentioning
confidence: 99%
“…The aforementioned studies indicate that different regions of the meniscus release different factors and substances that stimulate cells to differentiate into cells with different functions, but more research is needed to reveal the underlying mechanisms. Okuno et al reported that KI24RGDS peptide hydrogel facilitated meniscus repair in a rabbit meniscal defect model ( Okuno et al, 2021 ). In vitro and in vivo studies by Forriol et al and Ozeki et al demonstrated that bone morphogenetic protein-7 (BMP-7) is a suitable growth factor to stimulate meniscus regeneration and delay cartilage degeneration ( Ozeki et al, 2013 ; Forriol et al, 2014 ).…”
Section: Extrinsic Substance-delivery Hydrogelsmentioning
confidence: 99%
“…Self-assembled polypeptide hydrogels are normally stable and can aggregate spontaneously by forming non-covalent bonds between polypeptide molecules, such as hydrogen bonds, electrostatic interactions, and π-π stacking interactions. Okuno et al demonstrated that a self-assembling peptide hydrogel scaffold presented a repair and regeneration effect in the meniscus defect of a rabbit model ( Okuno et al, 2021 ).…”
Section: Meniscus Regeneration Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation